PTSD SYMPTOMS ACROSS PREGNANCY AND EARLY POSTPARTUM AMONG WOMEN WITH LIFETIME PTSD DIAGNOSIS. Issue 7 (6th January 2016) - Muzik, Maria; McGinnis, Ellen W.; Bocknek, Erika; Morelen, Diana; Rosenblum, Katherine L.; Liberzon, Israel; Seng, Julia; Abelson, James L.
Abstract : Background: Little is known about trajectories of PTSD symptoms across the peripartum period in women with trauma histories, specifically those who met lifetime PTSD diagnoses prior to pregnancy. The present study seeks to identify factors that influence PTSD symptom load across pregnancy and early postpartum, and study its impact on postpartum adaptation. Method: The current study is a secondary analysis on pregnant women with a Lifetime PTSD diagnosis ( N = 319) derived from a larger community sample who were interviewed twice across pregnancy (28 and 35 weeks) and again at 6 weeks postpartum, assessing socioeconomic risks, mental health, past and ongoing trauma exposure, and adaptation to postpartum. Results: Using trajectory analysis, first we examined the natural course of PTSD symptoms based on patterns across peripartum, and found four distinct trajectory groups. Second, we explored factors (demographic, historical, and gestational) that shape the PTSD symptom trajectories, and examined the impact of trajectory membership on maternal postpartum adaptation. We found that child abuse history, demographic risk, and lifetime PTSD symptom count increased pregnancy‐onset PTSD risk, whereas gestational PTSD symptom trajectory was best predicted by interim trauma and labor anxiety. Women with the greatest PTSD symptom rise during pregnancy were most likely to suffer postpartum depression and reported greatest bonding impairment with their infants at 6 weeks postpartum. Conclusions: Screening for modifiable risks (interpersonal trauma exposure and labor anxiety) and /or PTSD symptom load during pregnancy appears critical to promote maternal wellbeing.